2003
DOI: 10.1053/jhep.2003.50458
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for sustained HBeAg response to lamivudine therapy

Abstract: There are inconsistent data on the durability of hepatitis B e antigen (HBeAg) seroconversion after lamivudine is discontinued. The aim of this study was to examine the determinants for sustained HBeAg response to lamivudine therapy. Both host and viral factors as well as the drug factor were compared between 43 patients with sustained HBeAg response and 39 patients whose response was not sustained. All of them received a mean period of 16 months (range, 3-55 months) lamivudine therapy and had achieved complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
181
5
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(203 citation statements)
references
References 30 publications
12
181
5
4
Order By: Relevance
“…These data imply that HBV genotype may have no substantial impact on the response to lamivudine treatment. However, Chien et al reported that the sustained response rate to lamivudine was much higher in patients with genotype B than those with genotype C [123]. As to the emergence of drug resistance to lamivudine after prolonged therapy, we found that the development of lamivudine resistance was similar between genotypes B and C [119].…”
Section: Genotypesmentioning
confidence: 46%
“…These data imply that HBV genotype may have no substantial impact on the response to lamivudine treatment. However, Chien et al reported that the sustained response rate to lamivudine was much higher in patients with genotype B than those with genotype C [123]. As to the emergence of drug resistance to lamivudine after prolonged therapy, we found that the development of lamivudine resistance was similar between genotypes B and C [119].…”
Section: Genotypesmentioning
confidence: 46%
“…In our study, patients infected with genotype C achieved HBeAg seroconversion just as well as those infected with genotype B (32% vs. 30%, respectively). This is in contrast to CHB patients treated with lamivudine, where a higher sustained response has been previously noted in patients infected with genotype B (61%) than genotype C (25%, P = 0.009) [35]. This has particular importance for treating Asian patients, since genotype C was reported to have a high prevalence in studies of Korean patients and was associated with a lack of durability of HBeAg seroconversion [36,37].…”
Section: Discussionmentioning
confidence: 72%
“…The importance of a 6-to 12-month period of consolidation therapy to reduce the risk of relapse after HBeAg seroconversion has been demonstrated in patients with HBeAg-positive CHB [66,67]. In a study that examined determinants for sustained HBeAg responses to lamivudine therapy involving 82 HBeAg-positive CHB patients, an additional 8 months of lamivudine treatment (OR = 1.097; 95% CI = 1.028-1.171; P = 0.005), in addition to genotype B HBV (versus genotype C) and younger age, was an independent factor associated with sustained HBeAg response [66]. Similar findings were reported in a retrospective study that assessed factors predictive of posttreatment relapse after 12 months of lamivudine therapy in 461 Korean patients with CHB, mostly genotype C [67].…”
Section: Socioeconomic Impact Of Hbeag Seroconversion and The Abilitymentioning
confidence: 99%